Associating Liver Partition and Portal Vein Ligation for Primary Hepatobiliary Malignancies and Non-Colorectal Liver Metastases. (September 2016) - Björnsson, B.; Sparrelid, E.; Hasselgren, K.; Gasslander, T.; Isaksson, B.; Sandström, P.
Background and Aims: Associating liver partition and portal vein ligation for staged hepatectomy may increase the possibility of radical resection in the case of liver malignancy. Concerns have been raised about the high morbidity and mortality associated with the procedure, particularly when applied for diagnoses other than colorectal liver metastases. The aim of this study was to analyze the initial experience with associating liver partition and portal vein ligation for staged hepatectomy in cases of non-colorectal liver metastases and primary hepatobiliary malignancies in Scandinavia. Materials and Methods: A retrospective analysis of all associating liver partition and portal vein ligation for staged hepatectomy procedures performed at two Swedish university hospitals for non-colorectal liver metastases and primary hepatobiliary malignancies was performed. The primary focus was on the safety of the procedure. Results and Conclusion: Ten patients were included: four had hepatocellular cancer, three had intrahepatic cholangiocarcinoma, one had a Klatskin tumor, one had ocular melanoma metastasis, and one had a metastasis from a Wilms' tumor. All patients completed both operations, and the highest grade of complication (according to the Clavien-Dindo classification) was 3A, which was observed in one patient. No 90-day mortality was observed. Radical resection (R0) was achieved in nine patients, while the resection was R2 in one patient. The low morbidity and mortality observed in this cohort compared with those of earlier reports on associating liver partition and portal vein ligation for staged hepatectomy for diagnoses other than colorectal liver metastases may be related to the selection of patients with limited comorbidity. In addition, procedures other than associating liver partition and portal vein ligation for staged hepatectomy had been avoided in most of the patients. In conclusion, associating liver partition and portal vein ligation for staged hepatectomy can be applied to primary hepatobiliary malignancies and non-colorectal liver metastases with acceptable rates of morbidity and mortality.